A Comparative Study of Nanocellulose Isolation Methods from Palm Fiber for Functional Material Applications - Sukmawati Said; Ni Wayan Mega Savira Utami; Wahyuna Nur (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The high cellulose content and abundance of oil palm fiber make it an exceptionally promising sustainable source for nanocellulose production in advanced material science. This study executes a thorough comparative analysis of different isolation strategies covering chemical, mechanical, and enzymatic approaches to derive nanocellulose specifically for functional material development. We aim to clarify how each distinct isolation path dictates the final structural integrity, morphology, and thermal stability of the extracted nanocellulose. By synthesizing data through a systematic literature review, this research evaluates critical metrics such as the crystallinity index and fiber diameter, which directly influence the performance of functional composites. Our analysis reveals that while chemical techniques like acid hydrolysis are superior for achieving high crystallinity, mechanical processes like high-pressure homogenization provide enhanced aspect ratios despite their heavy energy demands. Additionally, enzymatic methods offer a greener pathway, though they often trade speed for environmental benefits. Ultimately, this comparative review serves as a strategic roadmap for researchers to select the most appropriate isolation method based on intended applications, ranging from high-strength bio-composites to flexible electronic components.